2006
DOI: 10.1016/j.ijpsycho.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Early time-locked gamma response and gender specificity

Abstract: The aim was to investigate whether gender is a causative factor in the gamma status according to which some individuals respond with time-locked, early gamma response, G+, while the others do not show this response, G-. The sample consisted of 42 volunteer participants (between 19 and 37 years of age with at least 9 years of education). There were 22 females and 20 males. Data were collected under the oddball paradigm. Auditory stimulation (10 ms r/f time, 50 ms duration, 65 dB SPL) consisted of target (2000 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…It can be speculated that males and females differ in their early stages of information processing that include visual sensory and perceptual operations, with no regard to the emotional content of the stimuli. This may be only true for visual stimuli, as for auditory stimuli no gender related differences in the evoked gamma response were observed (Karakaş et al, 2006). This finding is in concordance with findings on the behavioral level indicating a female superiority in perceptual speed, the ability to rapidly absorb the details of a visual stimulus, which has been recognized since the 1940s (e.g., Harshman, Hampson, & Berenbaum, 1983;Kim & Petrakis, 1998;Tyler, 1965;Wesman, 1949) and generalizes to many types of visual stimuli.…”
Section: Studysupporting
confidence: 83%
“…It can be speculated that males and females differ in their early stages of information processing that include visual sensory and perceptual operations, with no regard to the emotional content of the stimuli. This may be only true for visual stimuli, as for auditory stimuli no gender related differences in the evoked gamma response were observed (Karakaş et al, 2006). This finding is in concordance with findings on the behavioral level indicating a female superiority in perceptual speed, the ability to rapidly absorb the details of a visual stimulus, which has been recognized since the 1940s (e.g., Harshman, Hampson, & Berenbaum, 1983;Kim & Petrakis, 1998;Tyler, 1965;Wesman, 1949) and generalizes to many types of visual stimuli.…”
Section: Studysupporting
confidence: 83%
“…Proverbio et al (2006) published results on infant happy/distressed expression indicating much larger occipital P110 response in women compared to men. Karakaş et al (2006) used auditory stimulation and found that the differences in gamma band are independent of gender. We have to note that none of these studies considered a simple physiological stimulation; they have been focused rather on facial expression, also reflecting emotional behavior, attention and working memory.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these findings it has been suggested that early, time locked gamma is actually a sensory oriented process (Karakaş et al, 2006). In contrast to these findings, the late and non-phase locked gamma activity (occurring in the 200–500 ms window range) varies according to the levels of task complexity and stimulus (Herrmann & Mecklinger, 2000; Tallon-Baudry & Bertrand, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…In contrast to these findings, the late and non-phase locked gamma activity (occurring in the 200–500 ms window range) varies according to the levels of task complexity and stimulus (Herrmann & Mecklinger, 2000; Tallon-Baudry & Bertrand, 1999). These differences suggest that the late induced gamma response could be interpreted as perception process and higher cognitive function (Karakaş et al, 2006; Tallon-Baudry, 2003). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation